(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The term “pancreatic cancer” includes a group of malignant neoplasms that develop in the pancreatic parenchyma: head, body and tail of the pancreas. The main clinical manifestations of these diseases are abdominal pain, anorexia, weight loss, general weakness, jaundice [7,8].